FRI0710-HPR Objective and subjective measures of physical functioning in women with fibromyalgia: what type of measure is associated most clearly with subjective well-being? the al-Ándalus project. (12th June 2018) - Estevez-Lopez, F.; Acosta, F.M.; Acosta-Manzano, P.; Rodriguez-Ayllon, M.; Gavilán-Carrera, B.; Herrador-Colmenero, M.; Carbonell-Baeza, A.; Geenen, R.; Walitt, B.; Munguía-Izquierdo, D.; Pulido-Martos, M.
Abstract : Background: In fibromyalgia there is a discordance between performance-based (i.e., objective) and patient-reported (i.e., subjective) physical functioning (1, 2). However, it is unknown whether the association of physical functioning with health outcomes is different between objective and subjective measures. Objectives: To analyse the associations of the objective and subjective dimensions of physical activity, sedentary behaviour, and physical fitness with subjective well-being in women with fibromyalgia. Methods: This population-based cross-sectional study included 375 women with fibromyalgia from southern Spain. Physical activity, sedentary behaviour, and physical fitness were measured by questionnaires, accelerometers, and performance testing. Participants self-reported their levels of positive affect, negative affect, and satisfaction with life. Conservative multivariate analyses were used to analyse the association between these physical functioning measures and the assessment of affect and life satisfaction. Results: We found independent associations of the objective measures but not the subjective assessments of physical activity with positive affect and satisfaction with life (both, p <0.01 and adjusted R 2 >0.06) and of sedentary time with positive affect ( p <0.02 and adjusted R 2 >0.03). Moreover, we observed consistent and independent associations of both the objective and subjective dimensions of physical fitness with all the components of subjective well-being (all, p <0.01 and adjusted R 2 ranged from 0.02 to 0.05). Conclusions: Both objective and subjective measures of physical activity and sedentary behaviour independently impact affect and subjective well-being. Strategies to enhance both dimensions of physical fitness may be a promising approach for improving the subjective well-being in fibromyalgia. References: 1. Estévez-López F, et al. Disabil Rehabil2018;40(3):329–337. 2. Estévez-López F, et al. Rheumatology (Oxford)2017;56(11):2015–2024. Acknowledgements: This study was funded by the Spanish Ministries of Economy and Competitiveness [I+D+I DEP2013–40908-R, I+D+I DEP2010–15639, BES-2014–067612] and Education [FPU15/00002]. Disclosure of Interest: None declared